Characteristic of traditional market and spilled markets in Sungguminasa District and Surrounding. - Husain, Lidia; Baharuddin, Ichsan Invanni; Zhiddiq, Sulaiman; Musyawarah, Rahma (Universitas Negeri Makassar, 2018)
This study aims to: 1) To determine the condition of traditional market located in Sungguminasa and surrounding areas. 2) To determine the distribution of goods in these markets. 3) To determine the extent of the impact of the presence of adjacent markets in the region. The population in this study are all traders in Mamminasamaupa Market, Central Market Sungguminasa, Pallangga Markets, Markets and Market Kalegowa Panciro totaling about 1,070 traders. Sample drawn from the population as 107 traders with simple random sampling technique and the accidental sampling technique sampling haphazard manner until the desired data is met. The results showed that the location and condition of Sungguminasa Central Market, Market Mamminasamaupa, Pallangga Markets, Markets and Market Kalegowa Panciro shows the interaction between layout and layout layout residential market. The number of visitors in the market due to the inexpensive price karenya traded goods, especially vegetables. Distribution of goods originating from Gowa district and other districts in South Sulawesi. Some even come from outside the province of South Sulawesi. Negative impacts such as traffic congestion and litter are not organized regularly.